Recent advances of carbon nanotubes as electrocatalyst for in-situ hydrogen production and CO2 conversion to fuels - Grandprix T.M. Kadja; Moh. Mualliful Ilmi; St Mardiana; Munawar Khalil; Fuja Sagita; Neng T.U. Culsum; Adroit T.N. Fajar (Results in Chemistry, 2023)
In-situ hydrogen production and CO2 conversion to fuels have attracted significant attention as rational solutions to alleviate energy crises and climate issues. However, the implementation of such technology in large-scale industrial applications is still hampered by its inefficiency, considering the large energy barrier. Therefore, the fabrication of extremely efficient catalysts has become the main challenge in this field. Carbon nanotubes (CNTs) have recently been recognized as an encouraging electrocatalyst for such a process. CNTs-based electrocatalysts revealed remarkable catalytic activity in water-splitting reactions, proving that these materials are promising candidates for electrochemical processes. Carbon nanotubes with electron acceptor attributes facilitate charge separation, resulting in improved catalytic activity. This is primarily due to its exceptional physicochemical properties, i.e., enormous surface area, superior electrical conductivity, good thermal properties, and high melting point. This review highlights recent advances in the application of CNTs and CNTs-based catalysts in hydrogen production and CO2 conversion, focusing on detailed discussions on their preparation, modification, characterization, and catalytic performances. In addition, several possible challenges for further improvement of the CNTs catalytic system are also highlighted.